Extraction and purification of fucoxanthin from Malaysian brown seaweeds - Novinedri, Dedi; Jaswir, Irwandi; Mohd. Salleh, Hamzah; Miyashita, Kazuo (2010)
Seaweeds serve as an important source of bioactive natural substances. Seaweeds contain carotenoids, dietary fibres, proteins, essential fatty acids, vitamins and minerals. This study has been successfully conducted to extract, isolate and purifY jilcoxanthin, a class ofcarotenoid, ji'Olll two types of Malaysian brown seaweeds, namely Sargassum binderi and S. duplicatum, with the purity of fucoxanthin obtained up to 99.8%. Fucoxanthin content, total lipid, and fatty acid composition ofthe seaweeds were determined. Results showed that both samples contained a considerable amount ofjilcoxanthin and total lipid. The fucoxanthin and total lipid contents of S. duplicatum (l.0l±0.10 and 21.3±0.1 mg/ g dryweight, respectively) were significantly higher than those of S. binderi (0.73±0.39 and16. 6±4.1, respectively). Both types of seaweeds also contained a considerable amount of unsaturated fatty acids. However, in terms of docosahexanoic acid (DHA), eicosapentanoic acid (EPA), arachidonic acid (AA), linoleic acid (LA) and alpha-linolenic acid (ALA) contents, S. duplicatum was found to be higher (0.76, 2.55, 13.64, 5.81 and 5.35 %, respectively) than S. binderi (0.70, 1.82, 9.13, 6.37 and 4.39%, respectively). For saturated fatty acids, palmitic (C16:0) was found to be the major fatty acid in both samples studied.